2021
DOI: 10.1002/aenm.202101514
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy SWCNT Cathode for Aqueous Al‐Ion Battery Boosted by Multi‐Ion Intercalation Chemistry

Abstract: The aqueous Al‐ion battery has achieved great progress in recent years. It now shows comparable performance to that of even non‐aqueous Al‐ion batteries. However, it also shows relatively low energy output and there is limited general understanding of the mechanism behind this restriction to its practical application. Thus, the development of a high‐performance cathode material is in great demand. Herein, a high‐capacity single‐walled carbon nanotube (SWCNT) is developed as a cathode for the water‐in‐salt elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 64 publications
(62 reference statements)
0
22
0
Order By: Relevance
“…The Al/41 m AlCl 3 /SWCNT battery exhibited a specific capacity of 790 mAh g −1 at 5 A g −1 after 1000 cycles. [54] It showed two discharge plateaus of 1.8 and 1.2 V, which correspond to the deintercalation of AlCl 4 − and Cl − -assisted cointercalation of Al 3+ / H + , respectively. Apart from that, multi-ion intercalation of AlCl 4 − , Cl − , Al 3+ , and H + has also been carefully reviewed.…”
Section: Othersmentioning
confidence: 95%
“…The Al/41 m AlCl 3 /SWCNT battery exhibited a specific capacity of 790 mAh g −1 at 5 A g −1 after 1000 cycles. [54] It showed two discharge plateaus of 1.8 and 1.2 V, which correspond to the deintercalation of AlCl 4 − and Cl − -assisted cointercalation of Al 3+ / H + , respectively. Apart from that, multi-ion intercalation of AlCl 4 − , Cl − , Al 3+ , and H + has also been carefully reviewed.…”
Section: Othersmentioning
confidence: 95%
“…Leung's group further revealed the underlying mechanism. [64] They formulated a "water-in-salt" Al(NO 3 ) 3 electrolyte with HCl additive (Figure 5e). The existence of Cl À could assist the Al 3 + intercalation, resulting in a higher discharge plateau and improved performance.…”
Section: Electrolyte With Additivesmentioning
confidence: 99%
“…Reproduced with permission. [64] Copyright 2021, Wiley-VCH. (f) EIS plots obtained for Al//Al symmetric cells with different electrolytes.…”
Section: Hybrid Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pan et al developed a high-capacity single-walled carbon nanotube (SWCNT) as a cathode for Al-ion batteries, which delivered 790 mA h g −1 (based on the mass of SWCNT) at a current density of 5 A g −1 . 9 Lin et al reported amorphous anion-rich titanium polysulfides (a-TiS x , x = 2, 3 and 4) (AATPs) with a high concentration of defects. 10 The AATP cathodes, especially a-TiS 4 , achieved 206 mA h g −1 over 1000 cycles.…”
mentioning
confidence: 99%